Preprocedural statin therapy, inflammation, and myocardial injury in low‐risk stable coronary artery disease patients submitted to coronary stent implantation. Issue 2 (27th November 2015) - Greque, Gilmar V.; Serrano, Carlos V.; Strunz, Célia M.; Soeiro, Alexandre; Santos, Márcio; Pivateli, Flávio; Jacob, José Luis B.; Pesaro, Antonio Eduardo P.; Nicolau, José Carlos; Kalil‐Filho, Roberto
Abstract : Objective: Evaluate if statin therapy prior to elective coronary stent implantation (CSI) reduces the plasma levels of markers of inflammation and of myocardial necrosis in low‐risk stable coronary artery disease patients (CAD). Background: The elevation of markers of inflammation and of myocardial necrosis after percutaneous coronary intervention may interfere with clinical outcome. Among acute coronary syndrome patients, statins improve clinical outcomes when used before CSI—mostly due to reduction of CSI‐related myocardial infarction. However, little is known concerning preprocedural statin therapy on the reduction of these markers in stable patients at low‐risk. Methods: In this prospective, observational study, 100 patients ( n = 50 on statin therapy vs. n = 50 not on statin) with stable coronary artery disease underwent elective CSI. Inflammatory (C‐reactive protein [CRP], interleukin [IL]‐6, tumor necrosis factor‐α and matrix metalloproteinase‐9) and myocardial necrosis markers (troponin I and CK‐MB) were determined before and 24 hr after CSI. Results: All patients presented a significant increase of CRP and IL‐6 after CSI. However, this increase was attenuated in patients on statin therapy prior to CSI than those without statin therapy: 75% vs. 150% ( P < 0.001) and 192% vs. 300% ( P < 0.01). The other pro‐inflammatory markers were similar for both sets of patients. Troponin I and CK‐MB did not change after CSI regardless of previous statin therapy or not. Conclusions: Pretreatment with statin attenuates procedural inflammation, denoted by markedly lower increases of CRP and IL‐6 levels, in elective CSI within low‐risk stable CAD patients. Periprocedural myocardial injury was irrelevant and was not affected by preprocedural statin therapy in this population. © 2015 Wiley Periodicals, Inc.